2022
DOI: 10.1177/19714009221108673
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of patients with acute ischemic stroke and tandem occlusion due to internal carotid artery dissection: A multicenter experience

Abstract: Background The optimal management of patients with acute ischemic stroke (AIS) due to tandem occlusion (TO) and underlying carotid dissection (CD) remains unclear. Objective We present our multicenter-experience of endovascular treatment (EVT) approach used and outcomes for AIS patients with CD-related TO (CD-TO). Methods Consecutive AIS patients underwent EVT for CD-TO at five Italian Neuro-interventional Tertiary Stroke Centers were retrospectively identified. TO from atherosclerosis and other causes of, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Overall, 71 observational studies were potentially eligible for inclusion, and 34 reached qualitative synthesis (figure 1 for PRISMA flow-chart, online supplemental table 2 for study details). Among them, two observational studies compared noAPT versus SAPT,18 19 three compared noAPT versus DAPT,18 20 21 two compared noAPT versus GPI,18 19 five compared SAPT versus DAPT,18 22–25 four compared SAPT versus GPI18 19 26 27 and four compared DAPT versus GPI,18 28–30 while the remainder focused on a single APT regimen 31–50…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 71 observational studies were potentially eligible for inclusion, and 34 reached qualitative synthesis (figure 1 for PRISMA flow-chart, online supplemental table 2 for study details). Among them, two observational studies compared noAPT versus SAPT,18 19 three compared noAPT versus DAPT,18 20 21 two compared noAPT versus GPI,18 19 five compared SAPT versus DAPT,18 22–25 four compared SAPT versus GPI18 19 26 27 and four compared DAPT versus GPI,18 28–30 while the remainder focused on a single APT regimen 31–50…”
Section: Resultsmentioning
confidence: 99%
“…The majority of multicenter analyses show similar rates of recanalization and symptomatic ICH between the 2 approaches. 83,84 Most studies also report similar 90-day functional outcomes, but 1 retrospective study found better functional outcome with the retrograde approach. 85 Aspiration, angioplasty, and stenting have proved to be successful with equivalent outcomes in retrospective series.…”
Section: Hyperacute Treatmentmentioning
confidence: 97%
“…Although many studies report safety with stenting and even higher rates of vessel patency the day after mechanical thrombectomy, an improvement in functional outcome has not been found. [83][84][85]87,88 In randomized, multicenter studies of extracranial stenting, subgroup analysis of patients with cervical artery dissection failed to show a functional benefit after stent placement. 87,88 However, stenting of a stenotic or occluded dissected segment of the vessel can be considered to improve distal perfusion in patients with neurological deficits due to hypoperfusion.…”
Section: Acute Stentingmentioning
confidence: 99%
See 1 more Smart Citation